PEMBELAJARAN PEMAHAMAN KONSEP DALAM MENYELESAIKAN SOAL CERITA MATEMATIKA MATERI PECAHAN PADA SISWA KELAS IV DI SDIT LUQMANUL HAKIM BANDUNG - Siti Zulaikhah; Jajang Bayu Kelana (COLLASE (Creative of Learning Students Elementary Education), 2022)
This research is motivated by the low learning outcomes of the fourth grade students of SDIT Luqmanul Hakim Bandung in mathematics, one of which is in learning mathematics story problems. This type of research is a qualitative descriptive study with a case study design. The data was collected by means of test techniques, document analysis, and interviews with 40 students of research subjects. The data analysis technique used the Milles and Huberman model analysis. The data validity test was done by using triangulation techniques. The results showed that the research subjects made mistakes on each item with various types of errors, namely reading errors 8 times, misunderstanding problems 133 times, transformation errors 16 times, calculation process errors 50 times, and errors writing answers 3 times. There are 3 factors that cause students to make mistakes, namely: 1) difficulty understanding the problem; 2) do not understand the concept and operation of fractions; 3) and being forgetful and careless. The solution offered to minimize student errors in solving story problems is by increasing the practice of working on story questions, making story questions in more communicative language, applying cooperative learning in teaching story problems, and providing explanations using concrete props.